Удосконалення роботи служби медицини катастроф на прикладі Харківської області - Люлько, О.М. (Актуальні проблеми транспортної медицини, 2010)
Анализируя работу специалистов гражданской обороны в учреждениях здравоохранения Харьковской области, сделан вывод о целесообразности их оперативного подчинения органам службы медицины катастроф. В соответствии с этим, особенностью повышения квалификации в сфере гражданской обороны для этой категории специалистов, является создание курсов на кафедре медицины неотложных состояний, медицины катастроф Харьковской медицинской академии последипломного образования. Для проведения таких занятий це лесообразно привлечение специалистов из областного методического центра гражданской обороны. Analyzing work of specialists the civil defensive in establishments of health protection at the Kharkov region, a conclusion about expedience of their operative submission to the organs of service of medicine of catastrophes is done. In accordance with it, creation of courses on the department of medicine of the urgent states, medicine of catastrophes and military medicine of the Kharkov medicine academy of after diploma’s education is the feature of the in plant training in the field of
civil defensive for this category of specialists. For conducting of such employments bringing in of specialists from the regional methodical center of civil defensive is expedient.